2001
DOI: 10.1007/pl00000243
|View full text |Cite
|
Sign up to set email alerts
|

The effect of allergen-induced airway inflammation on airway remodeling in a murine model of allergic asthma

Abstract: These findings demonstrated that in this murine model airway eosinophilic inflammation is responsible for the development of airway remodeling as well as bronchial hyperresponsiveness in allergic bronchial asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
2
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 35 publications
11
102
2
4
Order By: Relevance
“…To determine the severity of the inflammatory cell infiltration, peribronchial cell counts were performed based on a fivepoint scoring system described by Myou et al (19). The extent of mucus production was quantified using a five-point grading system described by Tanaka et al (20).…”
Section: Histological Analysismentioning
confidence: 99%
“…To determine the severity of the inflammatory cell infiltration, peribronchial cell counts were performed based on a fivepoint scoring system described by Myou et al (19). The extent of mucus production was quantified using a five-point grading system described by Tanaka et al (20).…”
Section: Histological Analysismentioning
confidence: 99%
“…Briefly, the scoring system was: 0, no cells; 1, a few cells; 2, a ring of cells 1 cell layer deep; 3, a ring of cells 2-4 cells deep; 4, a ring of cells Ͼ4 cells deep. To determine the extent of mucus production, goblet cell hyperplasia in the airway epithelium was quantified blind using a 5-point grading system described by Tanaka et al (18). The adopted grading system was: 0, no goblet cells; 1, Ͻ25%; 2, 25-50%; 3, 50 -75%; 4, Ͼ75%.…”
Section: Histologic Examinationmentioning
confidence: 99%
“…Histological examination of lung tissue eosinophilia (A-D, magnification ϫ400) and mucus secretion (E-H, magnification ϫ 400) 24 h after the last challenge of saline aerosol (A and E), OVA aerosol (B and F), OVA aerosol plus PEG (C and G), or OVA aerosol plus 30 mg/kg U0126 (D and H). Quantitative analyses of inflammatory cell infiltration (I) and mucus production (J) in lung sections were performed based on the methods of Myou et al (17) and Tanaka et al (18), respectively. Lung tissues were fixed, sectioned at 7 m thickness, and stained with H&E for tissue eosinophilia or periodic acid-Schiff for mucus production.…”
Section: Figurementioning
confidence: 99%
“…Until now, it is reported that the decrease of eosinophil numbers in BALF was correlated with attenuation of asthma symptoms in animal models. 15,25) Many clinical studies have also documented a correlation between pulmonary eosinophilia and asthma, and the degree of eosinophils in BALF correlates with disease severity. 26) Thus, pulmonary eosinophilia has been closely related to asthma symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the extent of mucus production, goblet cell hyperplasia in the airway epithelium was quantified with a five-point grading system. 15,16) The adopted grading system was as follows: 0, no goblet cells; 1, Ͻ25%; 2, 25-50%; 3, 50-75%, and 4, Ͼ75%. The blinded quantitative analysis was performed with the described method previously.…”
Section: )mentioning
confidence: 99%